Gene action associated with heterosis expression in scarlet eggplant (Solanum gilo Raddi.) - Matos Andrade, Thiago; Lasmar, André; Maluf, Wilson Roberto; Gomes, Luiz Antonio Augusto; de Sousa Gonçalves, Ranoel José; Blank, Arie Fitzgerald (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2015)
The objectives of this work were to assess heterosis and its components in F1 hybrids of a diallel cross among lines of scarlet eggplants (Solanum gilo Raddi, syn. S. aeth opicum L.), and to study the modes of gene action associated with its expression. Six lines (Morro Redondo, Branco Comprido, BGH-1544, Tinguá, Irajá, Comprido Verde Claro) and 15 hybrids resulting from a diallel cross among them (reciprocals excluded) were tested in a randomized complete block design with four replications. Traits under study were total yield, mean fruit mass and fruit length/diameter ratio. There was no evidence of epistatic gene action in the expression of any of the traits under study. Heterosis for yield could be explained by overdominance, but higher yields were only weakly associated with larger frequencies of dominant alleles an indication that yields may be markedly influenced by the action of relatively few loci with overdominant gene action. Heterosis for mean fruit mass was associated with incompletely dominant gene action, and larger fruit mass was associated with larger proportions of dominant alleles. For fruit length/diameter ration (L.D-1), heterosis was due to incompletely dominant gene action, and dominant alleles were predominantly associated with lower L.D-1values.